Initiation and Persistence with Warfarin Therapy in Atrial Fibrillation According to Ethnicity - Malta Hansen, Carolina; Olesen, Jonas B.; Hansen, Morten L.; Azimi, Aziza; Torp-Pedersen, Christian; Dominguez, Helena (Frontiers in Pharmacology, 2012)
The aim of this study was to investigate initiation of and persistence with warfarin treatment in patients with atrial fibrillation according to ethnicity. Patients hospitalized with first-time atrial fibrillation from 1997-2009, prescription claims of warfarin and country of birth were identified by individual-level linkage of nationwide administrative agencies. Cox proportional hazards models were used to estimate the relationship between covariates affecting initiation and non-persistence with warfarin treatment. A total of 151,537 patients were included in the study and 5,061(3.3%) were of non-Danish origin. CHADS2 score distribution varied substantially according to ethnicity, the proportion of patients with CHADS2 score≥1 being 79.2%, 78.1%, 65.9% and 46.0% for patients of Danish, Western, Eastern and African origin, respectively. 79,239(52.4%) of all patients initiated treatment with warfarin at some point in time. Multivariable Cox proportional hazard analyses indicated patients of Eastern and African origin were less likely to initiate warfarin therapy (HR 0.75; 95% CI 0.69-0.82 and HR 0.58; 95% CI 0.44-0.76, respectively). Patients of Eastern origin were more likely to interrupt treatment (HR 1.23 95% CI 1.02-1.47; for all patients; HR 1.62 95% CI 1.22-2.16; for patients with CHADS2 score>1). African origin was associated with a trend to interrupt treatment (HR 1.44 95% CI 0.46-4.47; for patients with CHADS2 score>1). Initiation of and persistence with warfarin in atrial fibrillation patients is lower among patients of Eastern and African origin compared to patients of Danish and Western origin, despite equal access to health care and medication. Future studies should address, beyond ethnicity, all possible driving factors of (non)initiation and persistence with treatment in general. This will be particularly interesting in light of the new generation of anticoagulants, which might render different adherence to treatment.